Potential And Challenges of Blue Economy In Supporting Economic Growth In Indonesia: Literature Review - Humera; Rahmat Hidayat (Nusantara Journal of Multidisciplinary Science, 2024)
This study will discuss Indonesia's potential and challenges in developing a blue economy in increasing the country's economic growth. The issues that will be raised in this study include: (1) how much does Indonesia's blue economy support sector contribute to the economy; 2) what are the challenges of developing the blue economy in Indonesia; and 3) what strategies are being implemented by the government in developing the blue economy for a sustainable economy in Indonesia. Studies on the contribution of the marine, fisheries, and coastal tourism sectors to Indonesia's economic growth have been carried out several times. However, these studies are regional in nature or only focus on certain areas. Apart from that, the study above has not fully examined the supporting sectors for the blue economy in Indonesia. There are still few studies on the blue economy in Indonesia. This is because this concept is relatively new and Indonesia itself is still in the process of determining policies in implementing it. Studies in Indonesia on industrial sectors supporting the marine economy that have implemented the blue economy concept include those that still specifically study one industrial sector or are micro in nature